New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

Chalcopyrite as an indicator of uranium mineralization in the Qigequan deposit, western Qaidam Basin: Constraints from mineralogy, geochemistry, and sulfur isotopes - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Wen-Yi Wu; Chen Zhang; Zhe Chi; Zhi-Lin Cheng; Bin Guo; Yi-Fan Gao (Journal of Geochemical Exploration, 2026)

Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Multi-level optimized displacement field reconstruction in icebreaker structures using inverse finite element method - Sen Wan; Meng Zhang; Lin Ren; Zhaochun Zhang; Donghui Wang; Ding Chen; Xiaohui Zhang; Haibo Hu; Nan Li (Ocean Engineering, 2026)

ASFV early protein p30 suppresses antiviral type I IFN induction by targeting TRIM21 and RIG-I like receptor signaling adaptor MAVS - Jiajia Zhang; Hanrong Lv; Jin Ding; Ziyan Sun; Chenglin Chi; Sizhuang Liu; Sen Jiang; Nanhua Chen; Wanglong Zheng; Jianzhong Zhu (Veterinary Microbiology, 2026)

Fully coupled numerical model of moored structures-mooring line-ice ridge interaction - Jiaming Chen; Shengjie Rui; Sen Han; Shifeng Ding; Jie Tan; Li Zhou (Ocean Engineering, 2026)

Drosophila PcG-repressive deubiquitinase complex mediates antibacterial immune defense via transcriptional regulation of Calcineurin A1 - Umar Ali; Ruirui Tan; Sheng Hu; Sen Ding; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2026)

Optimal combination of iron/magnesium salts and urea can promote the degradation rate of maize straw by catalyzing the rapid de-polymerization of lignin - Han Li; Yuan fang Zhou; Sen Zhao; Si hui Yan; Ding hua Jia; Yan ping Zhang; Xiang dong Yang; Juan Li (Biocatalysis and Agricultural Biotechnology, 2026)

Linking bacterial community assembly to soil carbon metabolism under different thermal regimens - Sen LI; Weigen HUANG; Han HU; Haowei NI; Jixian DING; Zhiyuan MA; Mengting Maggie YUAN; Jizhong ZHOU; Jiabao ZHANG; Yuting LIANG (Pedosphere, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Characterization of a reassortant H3N2 swine influenza virus with 2009 pandemic internal genes and enhanced potential for zoonotic risk - Jun Jiao; Jin Ding; Ziyan Sun; Chenglin Chi; Sizhuang Liu; Sen Jiang; Nanhua Chen; Wanglong Zheng; Xiaoyan Ding; Jianzhong Zhu (Veterinary Microbiology, 2026)

Changes in production and fate of anthropogenic nitrogen driven by environmental policies in China - Yang Xu; Jiatao Chen; Sen Du; Yuming Sun; Wencheng Ding; Yandong Xue; Li Gao; Yong Chen; Xuan Zhou; Jiangpeng Hu; Zhiping Duan; Zengyuan Li; et al. (Journal of Environmental Management, 2026)

Synergistic mechanism of hydrophobic and hydrophilic antioxidants in the interface of tree peony seed oil bilayer emulsion - Wen-Sen He; Na Wei; Jingyu Li; Qingzhi Wang; Haonan Yang; Chen Tan; Shouhe Huang; Huafang Ding; Jianhua Zhu; Hanyu Zhu; Zhen-Yu Chen (Food Chemistry, 2026)

Paeoniflorin suppresses non-small cell lung cancer by interrupting FGF2-FGFR2-PI3K axis - Xuexue Shao; Bojiao Ding; Miaomiao Gao; Jiaying Li; Yujie Shi; Sen Chen; Mohamed Shahen; Yonghua Wang; Yan Li (Toxicon, 2026)

CFD-DEM-VOF numerical simulation for cavitation performance of the aft propeller in the brash ice channel - Anwen Zhang; Dongqin Li; Li Zhou; Fang Li; Shifeng Ding; Sen Han; Pentti Kujala (Ocean Engineering, 2026)

Research on effective trajectory planning, tracking, and reconstruction for USV formation in complex environments - Sen Han; Jiahao Sun; Lingxiao Yan; Shifeng Ding; Li Zhou (Ocean Engineering, 2025)

Drosophila proteasome subunit Rpn8 controls IMD pathway activation via PGRP-SC2 degradation - Mingfei Wu; Umar Ali; Sen Ding; Chuchu Zhang; Yiheng Jin; Xinyan Cao; Muhammad Abdul Rehman Saeed; Yangyang Zhu; Muhammad Usama; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2025)

Exploring the limit of Cu-based small-pore zeolite framework collapse during hydrothermal aging in NO abatement from diesel vehicle exhaust - Wenqing Ding; Yu Sun; Jinpeng Du; Zhongqi Liu; Jingjing Liu; Tongliang Zhang; Wenpo Shan; Xiaoyan Shi; Sen Xue; Xuewang Han; Yunbo Yu; Yulong Shan; et al. (Journal of Environmental Sciences, 2025)

Maximizing signal capacity via intrinsic damped vibration of anisotropic magnetized micropillars for wearable human-machine interface - Biao Qi; Yuanzhe Liang; Sen Ding; Dan Fang; Ming Lei; Qian Zhou; Chao Peng; Bingpu Zhou (Chemical Engineering Journal, 2025)

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

Adjustment of Effective Water Quality Evaluation Index for Subtropical Urban Rivers - Mengyue Zhang; Mingqiao Yu; Sen Ding; Zhao Li (Environmental Management, 2025)

Mechanisms of chemical corrosion in alumina-chromite refractories during e-waste recovery via pyrometallurgy - Shiliang Chen; Jian Wu; Xin Wang; Youqi Fan; Yuntao Yan; Xiutao Guan; Zhipeng Guo; Sen Zhao; Wenlong Tan; Chao Ding; Hongming Long (Journal of Environmental Chemical Engineering, 2025)

Unveiling the Hidden Impact: Hematoma Volumes Unravel Circuit Disruptions in Intracerebral Hemorrhage - Yingqing Wu; Qin Deng; Ranran Wei; Sen Chen; Fusheng Ding; Haipeng Yu; Ning Hu; Shilei Hao; Bochu Wang (Translational Stroke Research, 2025)

Synaptic-mitochondrial transport: mechanisms in neural adaptation and degeneration - Yang Ding; Huan Yang; Jie Gao; Can Tang; Yu-Yuan Peng; Xin-Mei Ma; Sen Li; Hai-Yan Wang; Xiu-Min Lu; Yong-Tang Wang (Molecular and Cellular Biochemistry, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Nicking endonuclease-mediated primer exchange reaction for rapid and sensitive miRNA detection - Fei Ding; Xiaomin Hang; Sen Tian; Wei Cao; Jingwen Wu; Li Wang (Analytica Chimica Acta, 2025)

Seasonal variations and hydrological management regulate nutrient transport in cascade damming: Insights from carbon and nitrogen isotopes - Yujing Yang; Wanfa Wang; Shengde Yu; Yuanbi Yi; Sen Xu; Yuanzhi Yao; Jun Zhong; Wenhong Shi; Sainan Chen; Qixin Wu; Zuhong Ou; Hu Ding; et al. (Water Research, 2025)

Enhancement of rice production and soil carbon sequestration utilizing nitrogen-fixing cyanobacteria - Sen Li; Weigen Huang; Chengrong Peng; Xiaoyan Jing; Jixian Ding; Tong Chen; Ruilin Huang; Han Hu; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Applied Soil Ecology, 2025)

COLREGs-Compliant autonomous collision avoidance and improved adaptive LOS-based motion control for USVs in complex waters - Ke Liu; Shifeng Ding; Lingxiao Yan; Jiahao Sun; Shidi Wu; Sen Han; Fang Li; Li Zhou (Ocean Engineering, 2025)

Hybrid trajectory planning and tracking for automatic berthing: A grid-search and optimal control integration approach - Sen Han; Lingxiao Yan; Jiahao Sun; Shifeng Ding; Fang Li; Feng Diao; Li Zhou (Ocean Engineering, 2025)

Recent progress of high-performance interconnectors for SOFC: From materials, protective coatings, optimizing strategies, towards the real stack applications - Yingzhen Hu; Desheng Li; Hu Guo; Sen-Hui Liu; Yu Meng; Shujiang Ding; Cheng-Xin Li (Chemical Engineering Journal, 2025)

Co-application of hydrothermal carbonization aqueous phase and biogas slurry reduced ammonia volatilization in paddy - Yimeng Wang; Haijun Sun; Yahui Ji; Yuanyuan Feng; Sen Chen; Shudong Ding; Yaxin Ma; Bingyu Wang; Yanfang Feng; Huifang Xie; Lihong Xue (Journal of Environmental Management, 2025)

Bioaccumulation and behavioral response patterns of crucian carp (Carassius carassius) after carbamazepine exposure and elimination - Wei Liu; Zhao Li; Feilong Li; Yuan Zhang; Sen Ding (Science of The Total Environment, 2024)

Automatic unberthing for underactuated unmanned surface vehicle: Model-based planning and control approaches in constricted harbors - Sen Han; Lingxiao Yan; Jiahao Sun; Shifeng Ding; Fang Li; Li Zhou (Ocean Engineering, 2024)

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

A study on ice resistance prediction based on deep learning data generation method - Qianyang Sun; Jiaming Chen; Li Zhou; Shifeng Ding; Sen Han (Ocean Engineering, 2024)

Single-Cell Sequencing Technology and Its Application in the Study of Central Nervous System Diseases - Yang Ding; Yu-Yuan Peng; Sen Li; Can Tang; Jie Gao; Hai-Yan Wang; Zai-Yun Long; Xiu-Min Lu; Yong-Tang Wang (Cell Biochemistry and Biophysics, 2024)

Intrinsic microbial temperature sensitivity and soil organic carbon decomposition in response to climate change - Sen Li; Manuel Delgado‐Baquerizo; Jixian Ding; Han Hu; Weigen Huang; Yishen Sun; Haowei Ni; Yanyun Kuang; Mengting Maggie Yuan; Jizhong Zhou; Jiabao Zhang; Yuting Liang (Global Change Biology, 2024)
Soil microbes are essential for regulating carbon stocks under climate change. However, the uncertainty surrounding how microbial temperature responses control carbon losses under warming conditions highlights a significant gap in our climate change models. To address this issue, we conducted a fine‐scale analysis of soil organic carbon composition under different temperature gradients and characterized the corresponding microbial growth and physiology across various paddy soils spanning 4000 km in China. Our results showed that warming altered the composition of organic matter, resulting in a reduction in carbohydrates of approximately 0.026% to 0.030% from humid subtropical regions to humid continental regions. These changes were attributed to a decrease in the proportion of cold‐preferring bacteria, leading to significant soil carbon losses. Our findings suggest that intrinsic microbial temperature sensitivity plays a crucial role in determining the rate of soil organic carbon decomposition, providing insights into the temperature limitations faced by microbial activities and their impact on soil carbon‐climate feedback.

Mechanism of propylene effect on the NH3-SCR performance of Cu-SSZ-13 catalyst - Wenqing Ding; Yu Sun; Jingjing Liu; Sen Xue; Xuewang Han; Zidi Yan; Yunbo Yu; Yulong Shan; Hong He (Chemical Engineering Journal, 2024)

Impact of H2O on CO2 adsorption and co-adsorption: Mechanism and high-performance adsorbents for efficient H2O-CO2 capture - Minghai Shen; Fulin Kong; Wei Guo; Zhongqi Zuo; Ting Gao; Sen Chen; Lige Tong; Peikun Zhang; Li Wang; Paul K. Chu; Yulong Ding (Chemical Engineering Journal, 2024)

Sublethal and transgenerational effects of broflanilide on Myzus persicae (Sulzer) (Hemiptera: Aphididae) - Sen-Wen Zhang; Qing-Hui Zeng; Hong Yang; Chao Zhang; Bo Ding; Han-Zhi Yang; Mao-Fa Yang (Crop Protection, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Analysis of Flow and Runner Dynamic Response Characteristics under Pump Conditions of Variable-Speed Pump Turbine - Linmin Shang; Jingwei Cao; Lei Wang; Shuang Yu; Sen Ding; Zichao Wei; Zhengwei Wang; Xiaobing Liu (Journal of Marine Science and Engineering, 2023)
Pumped storage power stations can ensure the safe operation of the grid, as well as utilize clean energy sources to establish a low-carbon, safe, and efficient energy system. As pump turbines, the core components of pumped storage power plants, become more and more popular, the technical requirements for hydraulic design begin to improve year by year. However, when the unit operates far beyond the optimal range, the variable-speed pump turbine can overcome the shortcomings of the fixed-speed unit and solve the problem of unstable operation under partial load. The pressure pulsation of the unit in the pump condition is investigated by numerical simulation, analyzing the hydraulic thrust, and studying the dynamic response characteristics of the runner at a maximum speed of 456.5 rpm. Comparing the pressure pulsation amplitude of various components in the entire flow passage, the highest values of pressure pulsation were found in the runner and vaneless space. The axial hydraulic thrust has a fluctuation range between 174t and 198t and 0t to 40t for radial force. As per the structural analysis, it has been observed that the runner demonstrates uneven patterns in both its axial and radial deformations, with deformation mainly concentrated in radial displacement and stress distribution mainly concentrated on the blades near the crown. The dynamic stress amplitude of the runner at monitoring point S1 (located on the runner blade near the crown) is 37 MPa. This stress has a dominant frequency of 4.8fn, while the monitoring point S2 (located on the runner blade near the band) is 4 MPa, and the dominant frequency is 1.8fn. Using these findings, the design of the variable-speed pump turbine’s runner can be optimized, and the unit’s stable and secure operation can be guided accordingly.

A Machine-Learning-Based Method for Ship Propulsion Power Prediction in Ice - Li Zhou; Qianyang Sun; Shifeng Ding; Sen Han; Aimin Wang (Journal of Marine Science and Engineering, 2023)
In recent years, safety issues respecting polar ship navigation in the presence of ice have become a research hotspot. The accurate prediction of propulsion power plays an important role in ensuring safe ship navigation and evaluating ship navigation ability, and deep learning has been widely applied in the field of shipping, of which the artificial neural network (ANN) is a common method. This study combines the scientific problems of ice resistance and propulsion power for polar ship design, focusing on the design of an ANN model for predicting the propulsion power of polar ships. Reference is made to the traditional propulsion power requirements of various classification societies, as well as ship model test and full-scale test data, to select appropriate input features and a training dataset. Three prediction methods are considered: building a radial basis function–particle swarm optimization algorithm (RBF-PSO) model to directly predict the propulsion power; based on the full-scale test and model test data, calculating the propulsion power using the Finnish–Swedish Ice Class Rules (FSICR) formula; using an ice resistance artificial neural network model (ANN-IR) to predict the ice resistance and calculate the propulsion power using the FSICR formula. Prediction errors are determined, and a sensitivity analysis is carried out with respect to the relevant parameters of propulsion power based on the above methods. This study shows that the RBF-PSO model based on nine feature inputs has a reasonable generalization effect. Compared with the data of the ship model test and full-scale test, the average error is about 14%, which shows that the method has high accuracy and can be used as a propulsion power prediction tool.

Antifungal effects of trans-anethole, the main constituent of Illicium verum fruit volatiles, on Aspergillus flavus in stored wheat - Jun-Dong Lei; Shuai-Bing Zhang; Wen-Zheng Ding; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu (Food Control, 2023)

Wearable patch with direction-aware sensitivity of in-plane force for self-powered and single communication channel based human-machine interaction - Dan Fang; Sen Ding; Ziyi Dai; Junwen Zhong; Bingpu Zhou (Chemical Engineering Journal, 2023)

Characteristics, seasonal variations, and dry deposition fluxes of carbonaceous and water-soluble organic components in atmospheric aerosols over China's marginal seas - Sen Zhao; Jianhua Qi; Xue Ding (Marine Pollution Bulletin, 2023)

Tomato recognition and location algorithm based on improved YOLOv5 - Tianhua Li; Meng Sun; Qinghai He; Guanshan Zhang; Guoying Shi; Xiaoming Ding; Sen Lin (Computers and Electronics in Agriculture, 2023)

Effects and mechanisms of extremely cold environment on body response after trauma - Yu-Yuan Peng; Xiu-Min Lu; Sen Li; Can Tang; Yang Ding; Hai-Yan Wang; Ce Yang; Yong-Tang Wang (Journal of Thermal Biology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Halogen microregulation in metal-organic frameworks for enhanced adsorption performance of ReO4-/TcO4- - Qing-Hua Hu; You-Gan Wang; Xin Gao; Yu-Zhen Shi; Sen Lin; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

The effect of volatile compounds of Syzygium aromaticum flower buds against Aspergillus flavus growth on wheat grain at postharvest stage - Yu-Liang Qin; Shuai-Bing Zhang; Wen-Zheng Ding; Yang-Yong Lv; Huan-Chen Zhai; Shan Wei; Ping-An Ma; Yuan-Sen Hu (Food Control, 2023)

Urban pipeline rainwater runoff is an important pathway for land-based microplastics transport to inland surface water: A case study in Beijing - Jiajia Zhang; Wencheng Ding; Guoyuan Zou; Xuexia Wang; Meng Zhao; Sen Guo; Yanhua Chen (Science of The Total Environment, 2023)

Water quality degradation drives the release and fractionation transformation of trace metals in sediment - Mingming Wang; Jie Ren; Aizhong Ding; Wende Zhao; Xiaojing Zhao; Weijiang Liu; Yijuan Bai; Liangsuo Ren; Sen Wang; Yi Wen; Bin Yang (Science of The Total Environment, 2023)

Low-dose tributyltin triggers human chondrocyte senescence and mouse articular cartilage aging - Yao-Pang Chung; Te-I Weng; Ding-Cheng Chan; Rong-Sen Yang; Shing-Hwa Liu (Archives of Toxicology, 2023)

Rare disperse elements in epithermal deposit: Insights from LA–ICP–MS study of sphalerite at Dalingkou, South China - Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Guo-Guang Wang; Jun-Ying Ding; Shu-Wu Chu; Wen-Sheng Li; Wen-Qing Huang; Ren-Zhi Zhu; Zhe Chi (Journal of Geochemical Exploration, 2023)

Distribution and microbial degradation of dissolved organic carbon in the northern South China Sea - Ling Ding; Sen Shan; Chunle Luo; Xuchen Wang (Frontiers in Marine Science, 2022)
Dissolved organic carbon (DOC) is the largest reduced carbon pool in the ocean, and it plays significant roles not only in the ocean carbon cycle but also in the control of many biogeochemical processes in the ocean. We present the concentrations and distribution of DOC in the northern South China Sea (SCS) and western North Pacific (NP) in the spring and summer seasons of 2015-2016 and 2019. Laboratory incubation bioassay experiments were also conducted to determine the microbiological respiration of DOC. In the SCS, the concentrations of DOC varied within a range of 38-95 μM, and the large spatial variations in DOC in the upper 100 m depth were influenced by a combination of factors, including primary production, terrestrial inputs from the Pearl River and the intrusion of the Kuroshio Current. The mesopelagic DOC distribution in the northern SCS basin was largely influenced by the physical mixing of upwelled deep water; however, biological processes were estimated to account for 6-20% of the modulation in DOC concentrations. Compared with the deep DOC levels in open ocean areas, a slightly excessive DOC concentration (~ 3-4 μM) was observed in the deep water of the SCS basin. Approximately 10-20% of the DOC was consumed by mesopelagic and/or deep water bacteria in the incubation bioassay experiments, and labile DOC was preferentially respired, resulting in decreased δ 13 C and Δ 14 C values of DOC.

Simulating the Effects of Conventional Tillage Versus No-Tillage on Nitrogen Uptake and Utilization of Winter Wheat with RZWQM2 in a 7-year Field Experiment - Jinli Ding; Sen Li; Wei Hu; Jicheng Wu; Yonghui Yang (International Journal of Plant Production, 2022)

Myosin light chain 2 marks differentiating ventricular cardiomyocytes derived from human embryonic stem cells - Xiao-Ling Luo; Peng Zhang; Xiangyuan Liu; Shiqian Huang; Sen-Le Rao; Qiurong Ding; Huang-Tian Yang (Pflügers Archiv - European Journal of Physiology, 2021)

Pleiotropic effects of Ubi4, a polyubiquitin precursor required for ubiquitin accumulation, conidiation and pathogenicity of a fungal insect pathogen - Ding‐Yi Wang; Kang Ren; Sen‐Miao Tong; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2020)
Summary Ubi4 is a polyubiquitin precursor well characterized in yeasts but unexplored in insect mycopathogens. Here, we report that orthologous Ubi4 plays a core role in ubiquitin‐ and asexual lifestyle‐required cellular events in Beauveria bassiana . Deletion of ubi4 led to abolished ubiquitin accumulation, blocked autophagic process, severe defects in conidiation and conidial quality, reduced cell tolerance to oxidative, osmotic, cell wall perturbing and heat‐shock stresses, decreased transcript levels of development‐activating and antioxidant genes, but light effect on radial growth under normal conditions. The deletion mutant lost insect pathogenicity via normal cuticle infection and was severely compromised in virulence via cuticle‐bypassing infection due to a block of dimorphic transition critical for acceleration of host mummification. Proteomic and ubiquitylomic analyses revealed 1081 proteins differentially expressed and 639 lysine residues significantly hyper‐ or hypo‐ubiquitylated in the deletion mutant, including dozens of ubiquitin‐activating, conjugating and ligating enzymes, core histones, and many more involved in proteasomes, autophagy‐lysosome process and protein degradation. Singular deletions of seven ubiquitin‐conjugating enzyme genes exerted differential Ubi4‐like effects on conidiation level and conidial traits. These findings uncover an essential role of Ubi4 in ubiquitin transfer cascade and its pleiotropic effects on the in vitro and in vivo asexual cycle of B. bassiana .

miR-663b promotes colorectal cancer progression by activating Ras/Raf signaling through downregulation of TNK1 - Sen Hong; Zhenkun Yan; Helei Wang; Lei Ding; Yumei Song; Miaomiao Bi (Human Cell, 2020)

Mapping and cloning of quantitative trait loci for phosphorus efficiency in crops: opportunities and challenges - Wei Wang; Guang-Da Ding; Philip John White; Xiao-Hua Wang; Ke-Mo Jin; Fang-Sen Xu; Lei Shi (Plant and Soil, 2019)

The effects of the Indo-Pacific warm pool on the stratosphere - Xin Zhou; Jianping Li; Fei Xie; Ruiqiang Ding; Yanjie Li; Sen Zhao; Jiankai Zhang; Yang Li (Climate Dynamics, 2018)

Simulation of the osmosis-based drug encapsulation in erythrocytes - Duobiao Ge; Lili Zou; Chengpan Li; Sen Liu; Shibo Li; Sijie Sun; Weiping Ding (European Biophysics Journal, 2018)

Decreased Expression of Selenoproteins as a Poor Prognosticator of Gastric Cancer in Humans - Xiuwen Lan; Jun Xing; Hongyu Gao; Sen Li; Lina Quan; Yang Jiang; Shaohua Ding; Yingwei Xue (Biological Trace Element Research, 2017)

Assessment of the effects of initial water contents on the pore pressure response of reconstituted clays - Xia Bian; Ling-Ling Zeng; Jian-Wen Ding; Sen Qian (European Journal of Environmental and Civil Engineering, 2017)

Relationships between the extratropical ENSO precursor and leading modes of atmospheric variability in the Southern Hemisphere - Jianhuang Qin; Ruiqiang Ding; Zhiwei Wu; Jianping Li; Sen Zhao (Advances in Atmospheric Sciences, 2017)

Interdecadal change in the lagged relationship between the Pacific–South American pattern and ENSO - Ruiqiang Ding; Jianping Li; Yu-heng Tseng; Kyung-Ja Ha; Sen Zhao; June-Yi Lee (Climate Dynamics, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Vaccination against type 1 angiotensin receptor prevents streptozotocin-induced diabetic nephropathy - Dan Ding; Yimei Du; Zhihua Qiu; Sen Yan; Fen Chen; Min Wang; Shijun Yang; Yanzhao Zhou; Xiajun Hu; Yihuan Deng; Shijia Wang; Liangping Wang; et al. (Journal of Molecular Medicine, 2016)

Differences in stream fish assemblages subjected to different levels of anthropogenic pressure in the Taizi River catchment, China - Yuan Zhang; Sen Ding; Catherine N. Bentsen; Shuqin Ma; Xiaobo Jia; Wei Meng (Ichthyological Research, 2015)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

A Comparative study on the nonspecific immunity of juvenile Litopenaeus vannamei ever inhabiting freshwater and seawater - Xuying Jia; Sen Ding; Fang Wang; Shuanglin Dong (Journal of Ocean University of China, 2014)

Comparison of the respiratory metabolism of juvenile Litopenaeus vannamei cultured in seawater and freshwater - Sen Ding; Fang Wang; Shuanglin Dong; Ying Li (Journal of Ocean University of China, 2014)

Inheritance of long staple fiber quality traits of Gossypium barbadense in G. hirsutum background using CSILs - Peng Wang; Yajuan Zhu; Xianliang Song; Zhibin Cao; Yezhang Ding; Bingliang Liu; Xiefei Zhu; Sen Wang; Wangzhen Guo; Tianzhen Zhang (Theoretical and Applied Genetics, 2012)

Construction of a eukaryotic expression vector pEGFP-C1-BMP-2 and its effect on cell migration - Xiao-ying Wang; Zhong-hua Chen; Ru-yi Zhang; Sen-quan Liu; Zhu Mei; Ying-ying Yu; Xiong Zhang; Qiang Xia; Yue-min Ding (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of salinity fluctuation frequency on the growth, molting rate and hemolymph 20-hydroxyecdysone concentration in Juvenile Chinese shrimp, Fenneropenaeus chinensis - Sen Ding; Fang Wang; Hao Sun; Shuanglin Dong (Journal of Ocean University of China, 2009)

Effects of salinity fluctuation frequency on the osmolarity, Na+-K+-ATPase activity and HSP70 expression in juvenile chinese shrimp, Fenneropenaeus chinensis - Sen Ding; Fang Wang; Hao Sun; Biao Guo; Shuanglin Dong (Journal of Ocean University of China, 2009)

Targeted delivery of therapeutics to endothelium - Eric Simone; Bi-Sen Ding; Vladimir Muzykantov (Cell and Tissue Research, 2009)